If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3y + 37 = 11 + -1y Reorder the terms: 37 + 6x + -3y = 11 + -1y Solving 37 + 6x + -3y = 11 + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + 6x + -37 + -3y = 11 + -37 + -1y Reorder the terms: 37 + -37 + 6x + -3y = 11 + -37 + -1y Combine like terms: 37 + -37 = 0 0 + 6x + -3y = 11 + -37 + -1y 6x + -3y = 11 + -37 + -1y Combine like terms: 11 + -37 = -26 6x + -3y = -26 + -1y Add '3y' to each side of the equation. 6x + -3y + 3y = -26 + -1y + 3y Combine like terms: -3y + 3y = 0 6x + 0 = -26 + -1y + 3y 6x = -26 + -1y + 3y Combine like terms: -1y + 3y = 2y 6x = -26 + 2y Divide each side by '6'. x = -4.333333333 + 0.3333333333y Simplifying x = -4.333333333 + 0.3333333333y
| -g+2(3+g)=-4(g-4) | | 2[w-(2w+10)+8]=2(w+2) | | 5(y-2)=6(y-1) | | 3(2k+18)=6(9+k) | | 4x^2+56x+156=0 | | s=4s-60 | | 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= |